2004
DOI: 10.1086/424571
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Measles Virus–Specific CD4 T Cell Memory in Vaccinated Subjects

Abstract: Since the licensure and generalization of an effective measles virus (MV) vaccine 41 years ago, antibody levels have been used as correlates of immunity. The long-lived MV-specific antibody response has been studied intensely, but the dynamics of MV-specific T cell immunity over time have not been well characterized. We thus characterized the profiles of MV vaccine-induced antigen-specific T cells over time since vaccination. In a cross-sectional study of healthy subjects with a history of MV vaccination, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 46 publications
3
45
0
Order By: Relevance
“…In this study, rubella antibody levels also lacked any correlation with measures of IL-10 (r ϭ 0.02, P ϭ 0.86) cytokine secretion. Similar disagreement in association between antibody levels to measles virus and IL-4 (r ϭ 0.04, P ϭ 0.45) secretion and measures of CD4 T-cell immunity was found in other studies (15,30). The complex interplay between genetic HLA polymorphisms, secreted cytokines, and measures of humoral and cellular immune responses to rubella vaccine currently precludes a validated model to explain these associations.…”
Section: Discussionsupporting
confidence: 56%
“…In this study, rubella antibody levels also lacked any correlation with measures of IL-10 (r ϭ 0.02, P ϭ 0.86) cytokine secretion. Similar disagreement in association between antibody levels to measles virus and IL-4 (r ϭ 0.04, P ϭ 0.45) secretion and measures of CD4 T-cell immunity was found in other studies (15,30). The complex interplay between genetic HLA polymorphisms, secreted cytokines, and measures of humoral and cellular immune responses to rubella vaccine currently precludes a validated model to explain these associations.…”
Section: Discussionsupporting
confidence: 56%
“…This is also similar to the measles vaccine (Naniche et al 2004) though both are thought to confer lifelong protection; neither has been demonstrated to persist into old age.…”
Section: Consequences Of Senescence On B Cell Functionmentioning
confidence: 55%
“…Although passive administration of antibodies protects an individual against natural infection even in the absence of a cellular response (2), the importance of cellular immunity in clearing infection has been well established for immunodeficient children (38). The relevance of serum antibodies to susceptibility or immunity remains an unsettled issue.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies have traditionally been used as markers of vaccine-induced immunity because they are easier to measure and quantify than cell-mediated immunity (38). Monitoring of humoral immunity is based upon detection of specific IgG antibodies, assessed mainly by immunoassays using the whole virus or recombinant proteins (10,12,20,26,49).…”
Section: Discussionmentioning
confidence: 99%